Relocation and Community Empowerment from the Perspective of the 1945 Constitution of the Republic of Indonesia - Abraham Ferry Rosando (Manunggal Halim Jaya, 2025)
The government often implements relocation policies to convert strategic areas into various development projects, purportedly for the common good. The implications of these policies often create tensions due to the dichotomy between the sovereignty of community living space over land and the state's authority to regulate land use. This study analyzes the alignment between the implementation of relocation policies and community empowerment efforts with the constitutional mandate outlined in the 1945 Constitution of the Republic of Indonesia. This study uses normative legal research methods with a conceptual and legislative approach to produce a prescriptive analysis. Based on this analysis, the study formulates policy principles that the government should consider. Furthermore, this study analyzes the legal relationships among land, buildings, and historical ownership, and their implications for relocation and empowerment policies.